Soiled Diapers Disposal Practices among Caregivers in Poor and Middle Income Urban Settings - Kimani, Emily Wambui; Muchiri, Joseph; Makindi, Stanley (International Journal of Scientific and Research Publications, 2015)
With the rise of Environmentalism in the 1960s, there was a growing realization by individuals, organizations and governments that the environment was being adversely affected by human activities. Nakuru for the last few years has seen a rapid population growth. This in turn, has seen an increase in the generation of non biodegradable solid waste. One type of such waste is disposable diapers. The purpose of this study was to investigate used diaper disposal practices among the care givers in Low and middle household income setting in Nakuru, Kenya. This type of setting was selected due to the fact that it houses the majority of the population. Specifically the study sought to identify the magnitude of diaper usage among this category of care givers as well as methods used in the disposal of the soiled diapers. The study also sought to determine the willingness of caregivers to make use of used diaper collection centre. This was a cross sectional research which used mixed research method methodology. Samples were taken from four low and middle income households in the town. Both quantitative and qualitative research method was used. Observational checklist and structured interview schedules with care givers were employed. Data analysis was done using Statistical Package for the Social Sciences version. The study established a high use of use of disposable diapers. Majority of the care givers disposed of diapers in the open field. Moreover, care givers were unwilling to transport used diapers to a collection centre. The study recommends that the public should be sensitized on the use of reusable diapers and need for separation of garbage from the source.
Keywords: Biodegradable; Diapers; Garbage; Nakuru